Implementation of Kaizen Culture in Human Resource Development at KB Permata Sunnah Sidoarjo - Arinda Prameswari; Hana Catur Wahyuni (CV. Media Digital Publikasi Indonesia, 2025)
Management is an important process in achieving goals through the coordination and supervision of others. In the context of Early Childhood Education (ECE), effective management is essential to ensure optimal education quality. Teachers play a central role in the success of education, yet a lack of discipline among teachers is often an obstacle. In the midst of increasing competition between schools, improving the quality of Human Resources (HR) is crucial. This article explores the application of Kaizen culture as a strategy to improve the quality of human resources at KB Permata Sunnah Sidoarjo. Kaizen, which focuses on continuous improvement through individual contributions, is applied to establish better work discipline and improve the quality of education. The results of the application of Kaizen are expected to create a more productive work environment and support the success of education in PAUD.